Mit „muzykalnego Wiednia” w twórczości krytycznomuzycznej Stefanii Łobaczewskiej - Magdalena Dziadek (Muzyka)
This paper presents a body of press sources relating to the influence of the myth of ‘musical Vienna’ on Stefania Łobaczewska’s critical writings on music. The author reconstructs the origins of that myth and its impact on the mentality of the residents of Lwów (now Lviv, Ukraine), with whom Łobaczewska identified. Łobaczewska’s remarks on the idiom of Viennese music are interpreted within the context of her characteristic views on national ideology and on the racial foundations of musical creativity, and then within the context of her general vision of the past, present and future of music in Europe.